Koshland’s model as a method for the analysis of enzymatic deracemization reactions - Verovka, О.S.; Kolodiazhna, А.О. (Reports of the National Academy of Sciences of Ukraine, 2021)
Koshland’s four-point location model is applied to consider some enzymatic reactions of deracemization. The sequential model is a theory describing the cooperativity of protein subunits. It postulates that the conformation of the protein changes with each binding of a ligand, thus sequentially changing its affinity to ligands at adjacent binding sites. When the substrate binds to the active site of one subunit of the enzyme, the remaining subunits are activated. The possibility of the alternative binding of both substrates and products of the enzymatic reaction can be assessed on the basis of the known data on the structure of all four substituents at the chiral atom and their correspondence to the ligand specificity of the corresponding subsets of the enzyme. The made theoretical conclusions were tested by the example of the enzymatic deracemization of some hydroxyphosphonic acids. The replacement of ethoxyl groups at the phosphorus atom by isopropoxy groups and an increase in the volume of the substituent led to a significant increase in the enantiomeric excess of the hydrolysis product of hydroxyphosphonate. Hence, the conclusion is drawn that the key criterion for the efficient or inefficient passage of the reaction is the ratio of the sizes and the degree of hydrophobicity of the corresponding substituents at the asymmetric reaction center.